Historical dictionary of the Spanish American War - Dyal, Donald H.; Carpenter, Brian B.; Thomas, Mark A. (Westport, Conn. : Greenwood Press, 1996)
Provides information on the naval and army operations, Spanish operations, and the political background to the military events, with an emphasis on future foreign affairs. Includes entries on people, places and events significant to the Spanish American War.
Includes bibliographical references (pages 363-364) and index.
Print version record.
Keywords: Spanish-American War, 1898 -- Dictionaries; HISTORY -- State & Local -- General; Spaans-Amerikaanse Oorlog; Spaanse koloniën.; 1898; Wars -- History, 1898-1902.; Cuba; Puerto Rico; Philippines; Electronic books; Dictionaries; Electronic books